Electrospun amphiphilic sulfonated poly(ether-ether-ketone) (SPEEK) membranes for thin-layer crude oil spill cleanup - Fuat Topuz; Zainah A. AlDhawi; Mahmoud A. Abdulhamid (Advanced Membranes)
Oil spills and the release of oily wastewater have caused serious damage to the environment and human health. Effective removal of oil spills and separation of oil/water mixtures have become a crucial step before they enter the environment and reveal their potentially harmful effects on aquatic ecology. In this context, herein, fibrous membranes based on sulfonated poly (ether-ether-ketone) (SPEEK) were produced and used for the adsorption of crude oils and their derivatives. PEEK was treated with H2SO4 at different times, and the concentrated solutions of the SPEEK were electrospun into bead-free nanofibers. The contact angle measurements with water and oils (i.e., crude oils, diesel, and gasoline) demonstrated the amphiphilic nature of the membranes. Depending on the crude oil sample used and the degree of sulfonation (DoS) of SPEEK, the crude oil sorption capacities ranged from 9 to 80 ​g ​g−1, while the adsorption capacities for gasoline and diesel were measured as 3 and 13 ​g ​g−1, respectively. As the DoS increased, the oil adsorption capacity of fibrous membranes declined due to the increased hydrophilicity of the membranes. Due to their amphiphilic nature, the SPEEK membranes could effectively remove even a thin layer of oil on seawater, a task that is challenging for most hydrophobic adsorbents. Fibrous SPEEK membranes could be employed as low-cost solutions for oil spill remediation and oil-in-water separation.